2011
DOI: 10.1177/0098628311411896
|View full text |Cite
|
Sign up to set email alerts
|

High-Tech Versus Low-Tech Instructional Strategies

Abstract: Although the use of clickers (classroom response systems) has been widely investigated, fewer studies directly compared outcomes for clickers with other active response methods, such as handheld response cards. We measured students' test performance and their self-reported anxiety and hope for upcoming tests after attending review sessions for an introductory psychology course. Students alternated using clickers and cards across the semester. Using clickers did not generally enhance test performance, reduce an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…As predicted, similar to previous research, (e.g., Anthis, 2011;Christopherson, 2011;Fallon & Forrest, 2011;Stowell & Nelson, 2007) no significant differences in student academic performance were found when comparing participants' exam scores across the different ASR modalities. However, exam scores were significantly higher for those students who utilized ASR methods when compared to students in the control condition.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…As predicted, similar to previous research, (e.g., Anthis, 2011;Christopherson, 2011;Fallon & Forrest, 2011;Stowell & Nelson, 2007) no significant differences in student academic performance were found when comparing participants' exam scores across the different ASR modalities. However, exam scores were significantly higher for those students who utilized ASR methods when compared to students in the control condition.…”
Section: Discussionsupporting
confidence: 90%
“…When designing a course, instructors have a variety of options for programming ASR, including raising hands to answer questions, holding up response cards (Heward, 1994;Randolph, 2007), utilizing electronic clickers (Kay & Lesage, 2009;Landrum, 2013), and several other approaches (e.g., reciprocal peer-tutoring, interteaching, etc.). Although a number of prior research studies have compared the effects of two response modalities (e.g., clickers versus hand-raising-Anthis, 2011; response cards versus clickers- Fallon & Forrest, 2011; response cards versus hand-raising- Kellum et al, 2001;Shaffer & Collura, 2009), few studies have directly compared three or more ASR techniques. Stowell and Nelson (2007) compared the effects of handraising, response cards, electronic clickers, and a control condition (standard lecture) on undergraduate student participation, quiz performance, and academic emotions (e.g., anxiety, hope, shame, enjoyment, etc.)…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Twyman et al [110] analysed how to improve student learning by using different strategies, such as clickers, response cards, and hand-raising. Findings obtained in an empirical investigation involving students attending an introductory psychology course concluded that students preferred to use SRSs over handheld response cards, although SRSs did not seem to improve the academic performance [111]. The validity and reliability for collecting data and associated psycho-social determinants for upper-elementary schoolchildren using SRSs is proved by Gray et al [112].…”
Section: Social Sciencesmentioning
confidence: 99%
“…One frequently reported advantage is the ability of an SRS to simulate interactions between students and the instructor in the classroom, thus increasing student willingness to engage in the class [1], [7]. Compared with other interactive methods (e.g., hand-raising and flashcards) that are generally used in large classrooms, most students tend to have a positive preference toward SRSs because they can effectively reduce the time spent for collecting individual responses in the classroom and offer the possibility of anonymity [9], [10], [11]. In addition, through posing various questions to students in the classroom, SRSs provide instructors with a clearer understanding of student learning issues including misunderstandings and inability to keep pace, allowing instructors to reexamine and adjust their course content and pace as necessary [3][10] [12].…”
Section: Introductionmentioning
confidence: 99%